Antimicrobial Susceptibility Patterns of Bacteria Associated With Hepatobiliary Disease in Dogs and Cats (2010–2019) - Alexandra T. Schlachet; Henri‐Jean Boulouis; Stéphanie Beurlet‐Lafarge; Morgane A. Canonne (Journal of Veterinary Internal Medicine)
ABSTRACT Background Description of antibiotic susceptibility of isolates from dogs and cats with hepatobiliary disease is limited. Objectives To describe antibiotic susceptibility patterns of bacteria associated with hepatobiliary disease in dogs and cats over a 10 year‐period. Animals Three hundred nine dogs and cats. Methods Bacterial species and antibiotic susceptibility data from positive bile and liver tissue cultures were reviewed from both a Veterinary Teaching Hospital and a private laboratory. Prevalence of multidrug‐resistant (MDR) bacteria was assessed, along with its association with previous antibiotic administration. Results A total of 343 bacterial isolates were included from 310 cultures. Monobacterial cultures were more frequent (91%, 283/310). Gram‐negative bacteria were predominant (67%, 227/340), with Escherichia coli (49%, 136/340), Staphylococcus spp. (14%, 47/340), and Enterococcus spp. (10%, 34/340) being the most prevalent isolates. Resistance of gram‐negative bacteria were: amoxicillin‐clavulanic acid (33%, 70/214), aminopenicillins (47%, 96/205), and fluoroquinolones (16%, 67/417); for gram‐positive bacteria: amoxicillin‐clavulanic acid (12%, 5/41), aminopenicillins (16%, 11/67), and fluoroquinolones (17%, 35/111). Resistance was significantly higher for aminopenicillins, first‐generation cephalosporins, TMPS, tetracyclines, and fluoroquinolones during 2010–2014 compared to 2015–2019. MDR isolates comprised 40% (135/430) of all isolates, 30% (41/136) of E. coli, and 68% (23/34) of Enterococcus spp. A significantly higher incidence of MDR bacteria was observed in animals with previous antibiotic treatment (81%, 17/21) compared to those without (30%, 22/75; p < 0.001). Conclusion and Clinical Importance Conducting culture and sensitivity testing remains crucial in dogs and cats suspected of hepatobiliary infection to ensure effective treatment.